A smart home system based on embedded technology and face recognition technology. Issue 3 (3rd July 2017) - Ai, Hong; Li, Tongliang
Abstract: A smart home module program is designed based on Linux, in the ARM11 embedded development environment, and by using the UP-Magic 6410 development board. A touch-screen graphical interface for human-computer interaction is designed using QT. The sensor module is integrated into the underlying QT program, and the actuator module program performs external calls via QT, thus a complete set of smart home terminal is constituted. The function of remote video monitoring and the function of displaying module statuses on webpage are realized through connecting video cameras to the development board as well as constructing GoAhead web server and Spcaserv video server. A face recognition program is designed using MATLAB, a database for storing the face information for different users is designed, and they are connected to the smart home terminal. Based on face recognition, the identity information for the current user and the desired temperature are displayed, and the speed of the DC motor is changed. This system can also realize sound and light alarm. Alarm for harmful gas can be raised under the help of smoke sensor. The photosensitive sound switch module is used for simulating the voice control device so as to facilitate the user's control of the DC motor switch. Infrared irradiation sensor is used for simulating the identity-card identification equipment, so as to limit the system users. Through the coordination of the above parts, a complete smart home system which is composed of a computer, embedded development environment, sensors, actuators and ancillary devices is finally established.